Dominant Factors of Recurrent Tuberculosis Treatment Visits in Jakarta: Faktor Dominan Kunjungan Berulang Pengobatan Tuberkulosis di DKI Jakarta - Della Dwi Ayu; Syarif Rahman Hasibuan; Putu Erma Pradnyani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Tuberculosis remains a major public health challenge in Indonesia, with DKI Jakarta designated as a priority province for tuberculosis control. Specific Background: Despite high treatment coverage, the treatment success rate in Jakarta declined from 81% in 2023 to 63.7% in 2025, far below the national target of 90%, indicating persistent problems in treatment adherence and continuity of care. Knowledge Gap: Although recurrent tuberculosis treatment visits are recognized as indicators of treatment failure and potential progression to drug-resistant tuberculosis, evidence regarding the dominant sociodemographic determinants of these visits in Jakarta remains limited. Aims: This study aims to analyze the association between sociodemographic factors—age, sex, and marital status—and recurrent tuberculosis treatment visits in DKI Jakarta. Results: A quantitative cross-sectional study using secondary BPJS Health data involving 46,064 tuberculosis patients was analyzed using logistic regression. The results show that marital status is the dominant factor associated with recurrent visits (p=0.000; OR=5.320). Age is also significantly associated, where individuals under 60 years have lower risk compared with those above 60 years, while sex shows no significant relationship (p=0.510). Novelty: This study identifies marital status as the main sociodemographic determinant of recurrent tuberculosis treatment visits using large-scale national health insurance data. Implications: The findings indicate that tuberculosis control strategies in DKI Jakarta should integrate family-based approaches by involving spouses as treatment supporters and utilizing educational tools such as the LEKAT leaflet to strengthen adherence monitoring and reduce recurrent treatment visits. Highlights • Marital status emerges as the strongest predictor of repeated tuberculosis treatment attendance.• Individuals aged under sixty years demonstrate lower probability of repeated therapy visits compared with elderly patients.• BPJS Health data analysis reveals demographic determinants supporting family-oriented tuberculosis control strategies. Keywords Tuberculosis; Recurrent Tuberculosis; Marital Status; Treatment Adherence; Public Health Surveillance